Empowering Women: Family Life Education Program for Poverty Alleviation - Nenden Rani Rinekasari; Elih Sudiapermana; Sardin Sardin; Yoyoh Jubaedah; Babang Robandi; Ace Suryadi (Journal of Innovation in Educational and Cultural Research, 2024)
The incidence of poverty in Indonesia has exhibited a marginal decrease, although it remains significantly distant from the desired objective and predominantly concentrated in rural regions. Efforts to reduce poverty should be optimized, particularly by prioritizing the economic empowerment of rural people and improving access to essential services. Poverty in Cianjur Regency, West Java Province, broadly impacted people's lives. Women in rural areas were a significantly affected group. It was among the five districts with the highest number of impoverished people in West Java. The study used secondary data analysis from 2005 to 2021 to understand poverty. This study employed a Concurrent Explanatory Design, which collected comprehensive interviews and statistical data. The researchers conducted interviews with the Head of the Neighborhood Association to gain insights into poverty at the local level. Additionally, they analyzed data from Statistics Indonesia on poverty, gender, and human development in Cianjur Regency from 2005 to 2021, spanning 16 years. The research sought to enhance comprehension of women's poverty in the region by integrating qualitative and quantitative methodologies. Human development index levels were low in Cianjur Regency due to poor development and limited gender empowerment. On average, women in the region had only 5.75 years of education, equivalent to the primary school level. The Family Life Education program was needed to empower families through education and training that suited their needs in addressing this issue. Thus, it was expected to reduce poverty and improve the condition of women in the Cianjur District.